Bipolar hemiarthroplasty in late-geriatric femoral neck fracture: Impact on survival and quality of life - Akbar, Muhammad Rifqi Farizan; Irianto, Komang Agung; Widajanti, Novira (Edelweiss Applied Science and Technology, 2025)
Femoral neck fractures in late geriatric patients pose significant challenges. This study aims to evaluate the effects of bipolar hemiarthroplasty on the 5-year survival rates and quality of life of late geriatric patients with femoral neck fractures. This longitudinal study involved patients over 75 years old who underwent bipolar hemiarthroplasty for femoral neck fractures. The Harris Hip Score (HHS) and the SF-12 were used to assess postoperative hip function and overall quality of life. The Charlson Comorbidity Index (CCI) was employed to evaluate comorbid conditions. Pearson or Spearman tests were used to measure the correlation between HHS, SF-12, and CCI. Kaplan-Meier survival curves were used to visualize survival trends. A total of 150 patients were included. The results of CCI and survival rate are CCI of 3 (mean 4.15 years); CCI of 4 (mean 4.10 years); CCI of 5 (mean 3.5 years); and CCI of 6 (mean 2.9 years). The most common preoperative condition among patients was Garden type III femoral neck fractures (56%). The hazard ratio increased by 1.398 (p = 0.005) as the CCI value increased. The survival rate for most patients in this study was over three years (52.6%). The average quality of life score for patients (Short Form-12) was 37.65 for physical components and 46.58 for mental components. Quality of life and hip function in late geriatric patients after bipolar hemiarthroplasty are low, with CCI linked to survival. This highlights the need for thorough preoperative evaluation and targeted rehabilitation.